Improvement of Technologies for Mining Waste Management (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Mining waste reduction methods include all mining processes beginning from resource distribution until final products in the plant. For comparing and testing possibilities of mine waste reduction, a cooperation project has been set up aiming to create a transnational network with regional networks. The activities carried out on the regional and transnational level will secure better access to knowledge, state-of-the-art technologies and good practice. The study addresses all the waste management challenges and opportunities facing the Baltic Sea Region mining industry, which should be understood as extending to all forms of extraction of natural non-renewable resources. In addition to the main mineral resource, oil shale, there are sufficient reserves of limestone and dolostone, peat, sand, gravel and clay. Phosphorite and granite are considered as occurrences in today's economic situation, in spite of the fact that phosphorite has been extracted for 70 years in the past. All previous mining activities have produced mining waste, e.g. the total volume of waste rock from Estonian oil shale mining is more than 76 million m3 and covers about 790 ha [31] [32] [33] [34]. From an environmental point of view Estonia is in good position, not having acidic reactions and having neutralising alkaline limestone present in all mining areas. Thanks to this, reclamation is easily done with the help of the same mining equipment. Water is purified in settling ponds and does not require additional chemical treatment. For underground mining, the main concern is the stability of the room and pillar mining area [35] [37]. Similar problems are found in Sweden and Finland. In Sweden, there are several old deposits from shale mining, the largest one (Kvarntorp) contains some 40 million m3 of crushed processed black shales and contains several metals of potential value.